Synthesis, characterization and biological activities of tridentate NNS schiff bases and their copper (II) complexes containing saccharin - Omar, Siti Aminah (2014)
New tridentate NNS Schiff bases derived from dithiocarbazate and thiosemicarbazide and their corresponding mixed-ligand copper(II) saccharinate complexes were synthesized. The Schiff bases as well as the copper(II) saccharinate complexes were characterized by elemental analysis, 1H and 13C NMR, mass spectrometry, conductance, magnetic susceptibility, IR, UV-Vis analysis and X-Ray diffraction analysis where appropriate. The spectral, mass spectrometry, 1H and 13C NMR analysis supported the formation of the Schiff bases. The structure of four of the Schiff bases and one of the complexes were further confirmed by X-Ray diffraction analysis. These include SB-4, S4M-4, S4M-5, 4M3T-4 and [Cu-4M3T5(sac)(H2O)]·Hsac. The copper(II) saccharinate complexes adopted either four or five coordinate geometry as suggested by magnetic and spectral analysis. The [Cu-4M3T5(sac)(H2O)]·Hsac complex was confirmed by X-Ray diffraction analysis to adopt a distorted square-pyramidal structure in which the Schiff bases coordinated to the copper(II) ion as tridentate NNS chelating agent via its azomethine nitrogen atom, thione sulphur atom and the pyridine nitrogen atom while the saccharinate anion coordinated as a unidentate N-donor ligand. The fifth coordination site is occupied by a water ligand. Interestingly, an un-coordinated saccharin was present outside of the coordination sphere. The Schiff bases and the complexes were tested for their cytotoxic properties towards MCF-7 (Estrogen receptor positive human breast carcinoma cells) and MDA-MB-231 (Estrogen receptor negative human breast carcinoma cells). The position of methyl group of the benzene ring was found to have an effect to the cytotoxic properties of the Schiff bases. All of the Schiff bases containing methyl group at the ortho position of the benzene ring were found to be inactive towards MDA-MB-231 cells, while having a methyl group at the para position increased the cytotoxicity of the Schiff bases. All of the copper(II) saccharinate complexes were moderately to highly cytotoxic towards both cell lines.